Understanding photoelectrochemical kinetics in a model CO2 fixation reaction. Issue 32 (5th August 2019) - Zhong, Bingju; He, Da; Chen, Ruonan; Gao, Tianyue; Wang, Yuanxing; Chen, Hongyu; Zhang, Yanhua; Wang, Dunwei
Abstract : The kinetics of photoelectro-catalytic fixation of CO2 has been studied in a model process, which reveals the rate-determining step and reaction order. Abstract : Kinetic studies of photo- and photoelectro-catalysis fixation of CO2 are rare. Herein, a typical CO2 reduction addition to trans -stilbene is studied. Through Tafel analyses, the reaction rate-determining step (RDS) is identified as the first step of an anion free radical generation from the substrate, and the reaction order is 0.5.